Severe gastrointestinal involvement in adult-onset Henoch–Schönlein purpura associated with clarithromycin-resistant Helicobacter pylori infection - Delgado García, Guillermo Rubén; Mandujano Cruz, Ilse; González Padilla, Kiber; Hernández Velázquez, Badir; Martínez Cabriales, Sylvia Aideé; Ocampo Candiani, Jorge; Villarreal Alarcón, Miguel Ángel; Galarza Delgado, Dionicio Ángel (2017)
Background: Henoch–Scho¨ nlein purpura (HSP) is an uncommon vasculitis in adults. Gastrointestinal involvement is part of the classical tetrad and can present as bleeding. Helicobacter pylori infection in the setting of HSP has been reported a few times in the literature and may be involved in the pathogenesis of this disease as a triggering agent. Case report: A 48-year-old man presented to the emergency department with 9 days of acute symmetric additive polyarthritis, 2 days of palpable purpura involving lower limbs, recent-onset intense mesogastric pain and hematochezia. H. pylori was detected in gastric tissue and triple therapy (clarithromycin, amoxicillin and omeprazole) was started. Gastrointestinal bleeding and other symptoms stopped 24 h after steroid initiation and he was later discharged on prednisone (1 mg/kg) and azathioprine (100 mg/day). Shortly after discharge he was readmitted with hematochezia and clarithromycin-resistant H. pylori infection was suspected. Bleeding stopped following reinstitution of corticosteroids and a second-line scheme (levofloxacin, amoxicillin and omeprazole) was introduced. Corticosteroids were gradually tapered and he remained on azathioprine. Nine months later he was doing fine. The pertinent literature is briefly discussed, highlighting the previous cases of concurrent diagnosis in adult patients. Conclusion: To the best of our knowledge, this is the first report describing resistance to clarithromycin-containing triple therapy in a H. pylori-infected adult patient with HSP. Gastrointestinal bleeding remains one of the most feared manifestations of HSP. These patients may benefit from H. pylori screening, as this might positively affect their prognosis. Further studies in adults are nevertheless needed to clarify this association and its therapeutic impact. 2016 Egyptian Society of Rheumatic Diseases. Publishing services provided by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc- nd/4.0/).